Assessment of the Nutrients in the Leachate and the Groundwater Quality for Drinking and Farming around the Nkolfoulou Landfill in Yaoundé, Cameroon - Gilbert Feuyit; John Ngolui Lambi; Estella Njoyim-Tamungang; Samuel Laminsi (Journal of Chemistry)
This study focuses on the assessment of the nutrients in the leachate and the groundwater quality around the Nkolfoulou landfill in Yaoundé known in French as “Centre de Traitement de Déchets (CTD).” Landfilling generates leachate that can pollute groundwater. Leachate along with groundwater samples (n=1+13) was collected in January (long dry season) and May (long wet season) 2014 and explored for various parameters including pH, temperature, EC, turbidity, TDS, TA, TSS, TH, BOD5, COD, Na+, K+, Mg2+, Ca2+, NH4+, NO3−, Cl−, F−, SO42−, PO43−, HCO3−, and colour using standard methods. In the leachate samples, values of TSS (700.2 and 130.2 mg/L), BOD5 (140 mg/L), COD (1350 and 1750 mg/L), NH4+ (82.50 and 39.51 mg/L), NO3− (159.32 and 74.82 mg/L), and Cl− (702.69 and 345.50 mg/L) exceeded the Cameroonian standards for effluent discharge. All the values of pH and some values of turbidity (4.55 and 4.50 NTU) and NH4+ (0.51 and 0.73 mg/L) in the groundwater samples violated the Cameroonian standards for drinking water. Based on the water quality index (WQI), an average of 11.53% of groundwater samples was improper for drinking in both seasons. Based on the parameters assessed, all the samples complied with the standard set for irrigation, poultry, and livestock. The hazard quotient (HQ) and the hazard index (HI) of NO3− and F− for children and adults were <1, and hence, the increased non-cancer risks due to these ions through the drinking of groundwater was low. From the statistical analysis, the Nkolfoulou landfill may not be the main source of major ions to the nearby groundwater.